Evidence for two independent domestications of cattle. - Loftus, R T (1994)
The origin and taxonomic status of domesticated cattle are controversial. Zebu and taurine breeds are differentiated primarily by the presence or absence of a hump and have been recognized as separate species (Bos indicus and Bos taurus). However, the most widely held view is that both types of cattle derive from a single domestication event 8000-10,000 years ago. We have examined mtDNA sequences from representatives of six European (taurine) breeds, three Indian (zebu) breeds, and four African (three zebu, one taurine) breeds. Similar levels of average sequence divergence were observed among animals within each of the major continental groups: 0.41% (European), 0.38% (African), and 0.42% (Indian). However, the sequences fell into two very distinct geographic lineages that do not correspond with the taurine-zebu dichotomy: all European and African breeds are in one lineage, and all Indian breeds are in the other. There was little indication of breed clustering within either lineage. Application of a molecular clock suggests that the two major mtDNA clades diverged at least 200,000, and possibly as much as 1 million, years ago. This relatively large divergence is interpreted most simply as evidence for two separate domestication events, presumably of different subspecies of the aurochs, Bos primigenius. The clustering of all African zebu mtDNA sequences within the taurine lineage is attributed to ancestral crossbreeding with the earlier B. taurus inhabitants of the continent.